2008
DOI: 10.1103/physrevlett.101.267601
|View full text |Cite
|
Sign up to set email alerts
|

Approaching the Dirac Point in High-Mobility Multilayer Epitaxial Graphene

Abstract: Multilayer epitaxial graphene is investigated using far infrared transmission experiments in the different limits of low magnetic fields and high temperatures. The cyclotron-resonance-like absorption is observed at low temperature in magnetic fields below 50 mT, probing the nearest vicinity of the Dirac point. The carrier mobility is found to exceed 250,000 cm2/(V x s). In the limit of high temperatures, the well-defined Landau level quantization is observed up to room temperature at magnetic fields below 1 T,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

42
415
4
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 613 publications
(475 citation statements)
references
References 37 publications
42
415
4
4
Order By: Relevance
“…21 The obtained v F ¼ 1.03(60.01) Â 10 6 m s À1 for our FLG is in a very good agreement with the results reported previously for decoupled C-face graphene on 4H-SiC. 13,14 Note that ABstacked inclusions, showing sub-linear dependence of the LL transition energy on the magnetic field, are commonly reported for C-face graphene on 4H-and 6H-SiC. 15,22 In contrast, no contribution from AB-stacked defects could be observed in our C-face graphene on 3C-SiC.…”
supporting
confidence: 88%
See 2 more Smart Citations
“…21 The obtained v F ¼ 1.03(60.01) Â 10 6 m s À1 for our FLG is in a very good agreement with the results reported previously for decoupled C-face graphene on 4H-SiC. 13,14 Note that ABstacked inclusions, showing sub-linear dependence of the LL transition energy on the magnetic field, are commonly reported for C-face graphene on 4H-and 6H-SiC. 15,22 In contrast, no contribution from AB-stacked defects could be observed in our C-face graphene on 3C-SiC.…”
supporting
confidence: 88%
“…13,14 Recently, we have shown that infrared optical Hall effect (OHE) measurements, which comprise performing generalized spectroscopic ellipsometry in the presence of a magnetic field, are an excellent tool to carry out LL spectroscopy in FLG. 15,16 In this work, we combine the infrared OHE with lowenergy electron microscopy (LEEM) and micro low-energy electron diffraction (l-LEED) investigations to study the interaction between individual layers, their electronic properties, and the stacking order in FLG grown on the C-face of 3C-SiC(111).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Comparing to mechanical exfoliation of graphene from graphite, large area epitaxial growth of graphene layers on silicon carbide (SiC) surface shows huge application potentials and has apparent technological advantages over the mechanical exfoliation method 6,7 . In this letter, we demonstrate that substitutional doping could be strongly enhanced in epitaxial graphene grown on SiC substrate comparing to that of free-standing graphene (FSG).…”
Section: Fig 1: (Color Online)mentioning
confidence: 99%
“…1 Though graphene provides extremely high mobility and electrical conductivity, its semi-metallic properties limit wide application in modern electronics. 2 Transition-metal dichalcogenides are, on the other hand, semiconductors with a graphene-like hexagonal structure in single or multiple layers. 3 Their band gaps, ranging approximately 1.0-2.5 eV, are normally at the K point in the Brillouin zone when direct.…”
mentioning
confidence: 99%